Association between CFL1 gene polymorphisms and spina bifida risk in a California population - Lammer Edward J; Shaw Gary M; Ma Chen; Enaw James; Zhu Huiping; Finnell Richard H (BMC, 2007)
Abstract Background CFL1 encodes human non-muscle cofilin (n-cofilin), which is an actin-depolymerizing factor and is essential in cytokinesis, endocytosis, and in the development of all embryonic tissues. Cfl1 knockout mice exhibit failure of neural tube closure at E10.5 and die in utero. We hypothesized that genetic variation within the human CFL1 gene may alter the protein's function and result in defective actin depolymerizing and cellular activity during neural tube closure. Such alterations may be associated with an increased risk for neural tube defects (NTDs). Methods Having re-sequenced the human CFL1 gene and identified five common single nucleotide polymorphisms (SNPs) in our target population, we investigated whether there existed a possible association between the genetic variations of the CFL1 gene and risk of spina bifida. Samples were obtained from a large population-based case-control study in California. Allele association, genotype association and haplotype association were evaluated in two different ethnicity groups, non-Hispanic white and Hispanic white. Results Homozygosity for the minor alleles of the SNPs studied (rs652021, rs665306, rs667555, rs4621 and rs11227332) appeared to produce an increased risk for spina bifida. Subjects with the haplotype composed of all minor alleles (CCGGT) appeared to have increased spina bifida risk (OR = 1.6, 95% CI: 0.9~2.9), however, this finding is not statistically significant likely due to limited sample size. Conclusion The sequence variation of human CFL1 gene is a genetic modifier for spina bifida risk in this California population.